Efficacy of Bile Acid Sequestrants in Treating Bile Acid Diarrhea: A Double Blind, Placebo-Controlled RCT - Muhammad Rehman Afzal, Syed Osama Talat, Jahanzaib, Mian Sajjad Ahmad, Shahzad Latif, Attiya Arif (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A double-blind, placebo-controlled randomized clinical trial evaluated the efficacy of colesevelam1.875 g twice daily in adults with bile-acid diarrhea (BAD) confirmed by SeHCAT retention≤10 %. Eighty participants were randomized